2013
DOI: 10.1007/s00726-013-1542-9
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products (AGEs) are cross-sectionally associated with insulin secretion in healthy subjects

Abstract: It has been postulated that chronic exposure to high levels of advanced glycation end products (AGEs), in particular from dietary sources, can impair insulin secretion. In the present study, we investigated the cross-sectional relationship between AGEs and acute insulin secretion during an intravenous glucose tolerance test (IVGTT) and following a 75 g oral glucose tolerance test (OGTT) in healthy humans. We report the cross-sectional association between circulating AGE concentrations and insulin secretory fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
2
20
0
1
Order By: Relevance
“…In support of our findings that lower serum CML is associated with greater insulin resistance, obese humans with evidence of very early metabolic dysfunction and insulin resistance also have lower circulating serum protein-bound AGE concentrations such as CML (6,23,24). The significance of this decrease in protein-bound CML before overt hyperglycemia remains to be determined.…”
Section: Discussionsupporting
confidence: 68%
“…In support of our findings that lower serum CML is associated with greater insulin resistance, obese humans with evidence of very early metabolic dysfunction and insulin resistance also have lower circulating serum protein-bound AGE concentrations such as CML (6,23,24). The significance of this decrease in protein-bound CML before overt hyperglycemia remains to be determined.…”
Section: Discussionsupporting
confidence: 68%
“…An animal study demonstrated that exposure to excess AGEs activates pathways of β -cell damage which, via mitochondrial superoxide generation, can impair insulin secretion [4]. A human study also showed a cross-sectional association between AGEs and acute insulin secretion during glucose tolerance testing in healthy humans [5]. Another human study demonstrated that the circulating level of AGEs is associated with insulin resistance as evaluated by the homeostasis model assessment for insulin resistance (HOMA-IR), even in nonobese, nondiabetic subjects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ivancovsky‐Wajcman et al have suggested that serum sRAGE levels are associated with NAFLD that may function as a protective factor against RAGE in the AGEs‐RAGE/sRAGE system. Moreover, previous studies showed that CML accumulates much more pronounced in human fatty livers, where it is decomposed and secreted into the bloodstream as an unstable component. However, the association of circulating CML in serum with NAFLD is not known.…”
Section: Discussionmentioning
confidence: 99%